(untitled) - Shively, W. Phillips (Boston, 2005)
Known for its comparative approach and its strong balance between theory and practical real-world examples, POWER AND CHOICE continues as a best-seller, offering a brief but rich introduction to Political Science. Organized topically, this text maintains its use of extended examples of appropriate countries and its strong underlying theme: the contrasting purpose of political institutions as a means to acquire power versus its use as a means to exercise public choice. POWER AND CHOICE serves especially well where instructors wish to use a core text supplemented with additional readers, handouts, or other classroom materials.
Keywords: Khoa học chính trị,Political science